Prevalência da infecção pelo vírus da hepatite C e práticas de risco em homens que fazem sexo com homens em Goiânia-Goiás, empregando o método respondent-driven sampling (RDS) - Andrade, Andreia Alves de (2016)
Hepatitis C is the most common cause of chronic liver disease. Men who have sex with men (MSM) may be at increased risk of acquiring infections transmitted by parenteral and sexual routes, such as hepatitis C. Despite the relevance of this subject, only one investigation regarding hepatitis C virus (HCV) infection in MSM was conducted in Brazil. Therefore, this study aimed to investigate the prevalence of HCV infection and risk practices among men who have sex with men in the City of Goiânia, Goiás. Cross-sectional study conducted in 522 MSM in Goiania, recruited by respondent-method driven sampling (RDS), from March to November 2014. After signing the informed consent, participants were interviewed about sociodemographic and risk behaviors/practices for HCV infection and then blood samples collected. All samples were subjected to determine the levels of alanine aminotransferase and aspartate aminotransferase (ALT and AST) and anti-HCV marker detection. Samples that had high levels of ALT/AST and/or were anti-HCV positive were tested for HCV RNA by reverse transcription-polymerase chain reaction (RT-PCR), and the positive samples were genotyped by a line probe assay (LiPA). Of 522 samples, four were anti-HCV positive and 14 had high levels of ALT/AST. Of these, only two (Y-421/anti-HCV positive and Y-180/anti-HCV negative/elevated ALT and AST) were HCV RNA positive, and then were genotyped by LiPA as genotype 1, subtypes 1a and 1b. Thus, five samples were anti-HCV and/or HCV RNA positive, resulting in an adjusted prevalence of 1.71% (95% CI: 0.32-8.55) for HCV infection among MSM in Goiânia-GO. Despite it is a low prevalence, many risk behaviors/practices were reported by the studied individuals (tattoo/piercing, sharing of personal hygiene tools, illicit drug use, multiple sexual partners in lifetime, sex with more than one partner in the same relationship, sex with a drug user partner, non-use or occasional condom use during anal sex, alcohol/drug use during sex, among others), which may characterize the target population as potentially vulnerable to infectious diseases transmitted by parenteral and sexual routes.